Crystal Growth and Glass-Like Thermal Conductivity of Ca3RE2(BO3)4 (RE = Y, Gd, Nd) Single Crystals - L. V. Gudzenko; M. B. Kosmyna; A. N. Shekhovtsov; W. Paszkowicz; A. Sulich; J. Z. Domagała; P. A. Popov; S. A. Skrobov (Crystals, 2017)
Crystal growth and thermal properties of binary borates, Ca3RE2(BO3)4 (RE = Y, Gd, Nd), are considered promising crystals for laser applications. These single crystals were grown by the Czochralski method. The crystal and defect structure were characterized. Volumetric chemical methods without prior separation of the components were developed and applied for the determination of the dependence of chemical compositions of the crystals on the growth conditions. The thermal conductivity was investigated in the 50–300 K range. The character of the temperature dependence of thermal conductivity was found to be similar to that of glass. The possible reasons of the observed features of the thermal conductivity were analyzed.